Pengaruh Media Kartu Angka Terhadap Kemampuan Berhitung Pada Anak Usia 3-4 Tahun Di Kelompok Bermain Az-Zahwa - Sulistina, Reni (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2024)
This study was motivated by the importance of the ability of number concepts in Az-zahwa Playgroup, especially at the age of 3-4 years, which is still low. In the initial observation conducted at Az-zahwa Playgroup when the mathematics learning process was taking place, children were asked to mention the sequence of numbers, children were unable to do it, some children were unable to count and point to objects, children were also unable to connect / pair number symbols with objects, some children could not write numbers 1-10. This study aims to determine how much influence the use of number card media has on the ability of number concepts in children aged 3-4 years at Az-zahwa Playgroup. The method used in this study is quantitative with an experimental method. The experimental design used is a pre-experimental design with a one-group pretest-posttest design. The results of the t-test hypothesis test where the t_count was obtained 37.648 the results were then compared with the t_table of the t distribution, the sig. level 0.05 for t table 0.05:15 so that the t_table was obtained 1.756 meaning t_count> t_table then H_O is rejected and H_a is accepted. so it can be concluded that the Number Card Media is accepted which means there is an influence of the use of number card media on children's counting skills.